Integrated Thermoelectric Cooling for Silicon Photonics. (16th February 2017) - Enright, R.; Lei, S.; Cunningham, G.; Mathews, I.; Frizzell, R.; Shen, A.
Abstract : Integrated silicon photonics has emerged as a scalable optoelectronic platform to meet the demands for increased bandwidth in communication networks. However, integration introduces new thermal challenges to achieving the required system performance. Here we present the design of a micro thermoelectric temperature controller integrated around a III-V-on-silicon hybrid waveguide. We briefly outline the thermal requirements to ensure suitable hybrid laser performance for a long reach optical communication application on a silicon photonics platform, namely an active region temperature of ≤ 54°C. We then develop a multiphysics numerical model of a micro thermoelectric temperature controller integrated around the waveguide and assess our design in terms of ambient operating temperatures of 80°C relevant for an integrated optoelectronic system. Our simulations indicate that state-of-the-art electrodeposited bismuth telluride can achieve the required refrigeration with suitable system design optimization. Despite characteristically low cooling efficiencies compared to a macroscopic thermoelectric module solution, considering overall system energy consumption shows that targeted refrigeration using our integrated thermoelectric design can be beneficial when cooling up to ∼20% of the overall system thermal load. Our results show the promise of integrated thermoelectric temperature control to meet the thermal requirements for integrated silicon photonics under realistic operating conditions.